Theoretical basics of radiant heat transfer – practical examples of calculation for the infrared (IR) used in infrared thermography measurements. Issue 4 (8th August 2021) - Minkina, Waldemar
ABSTRACT: The article presents the theoretical basics and definitions of radiant heat transfer with practical examples of calculation for the infrared (IR) used in infrared thermography measurements. In order to illustrate the practical possibilities of using the theoretical basics described for radiant heat transfer, the article presents some original, useful and practical examples including author's methods regarding these calculations.